Evaluation of tourism competitiveness and analysis of obstacle factors in border counties of Northeast China - Yue Gong; Shan Man; Wei Liu (Frontiers in Public Health, 2026)
Border counties often face challenges in transforming tourism resources into sustainable development advantages due to constraints in economic conditions, accessibility, public services, and environmental quality. However, existing tourism competitiveness studies have mainly focused on resource endowment and economic performance, with limited attention to environmental health and public service support as foundations for sustainable tourism development. This study develops a multidimensional framework incorporating Tourism Economic Development, Tourism Resource Attractiveness, Environmental Health, Accessibility and Supporting Infrastructure, and Tourism Service and Public Service Support to evaluate tourism competitiveness in 33 border counties of Northeast China from 2014 to 2023. The Criteria Importance Through Intercriteria Correlation (CRITIC) weighting method and the VIKOR evaluation model were used to measure tourism competitiveness, and an obstacle degree model was applied to identify key constraints and their evolution. The results show that tourism competitiveness in Northeast China’s border counties generally improved, although disparities among counties remained pronounced. Competitiveness levels shifted upward overall, with a gradual increase in high-competitiveness counties distributed across multiple locations in all three provinces. The dominant constraints also shifted from inadequate Tourism Service and Public Service Support toward limitations in Tourism Economic Development, resource transformation, and accessibility. Environmental Health was less frequently identified as a dominant obstacle but remained an important foundation for sustainable tourism development by supporting destination quality and resilience. This study provides insights into sustainable border tourism development by integrating Environmental Health and public service dimensions into tourism competitiveness assessment.